Elucidating the role of pyrabactin-like receptors of finger millet under drought and salinity stress: an insight into in silico, machine learning and molecular approaches - Rani, Varsha; Maharajan, Theivanayagam; Singh, Shefali; Joshi, D. C.; Gupta, Ramwant; Yadav, Dinesh (Frontiers in Genetics, 2025)
IntroductionThe Pyrabactin Resistance 1-like (PYL) receptors, a family of proteins in plants, play a vital role in abscisic acid (ABA) signalling, assisting plants in managing abiotic stresses. Finger millet (Eleusine coracana (L.) Gaertn) is a naturally drought tolerant crop, yet the receptor proteins involved in its stress signalling pathways remain poorly understood.MethodThis study employed bioinformatics, machine learning, and molecular approaches to identify, characterize, and profile the expression of PYL receptors in response to drought and salinity stress.ResultsThe study identified 14 PYL genes in the finger millet genome, irregularly distributed across four of the nine mapped chromosomes. Phylogenetic analysis grouped these genes into three subfamilies. Machine learning analysis highlighted five putative PYL genes—EcPYL4-2A, EcPYL7-2B, EcPYL11-5A, EcPYL12-5A, and EcPYL14-5B with expression levels exceeding 70% under drought and salinity stress. These genes were further validated through qRT-PCR, confirming their expression under stress conditions, though expression levels varied across tissues and genes.Discussion The identification of PYL genes responsive to drought and salt stress provides valuable insights into the stress-signalling mechanisms of finger millet. Among the identified genes, EcPYL7-2B and EcPYL12-5A emerged as promising candidates for further characterization through genome editing and molecular approaches. This study highlights the potential of these genes in enhancing the stress resilience of finger millet, contributing to its role in improving food and nutritional security under challenging environmental conditions.